Influence of Intracerebral Hemorrhage Location on Incidence, Characteristics, and Outcome: Population-Based Study. Issue 2 (February 2015) - Samarasekera, Neshika; Fonville, Arthur; Lerpiniere, Christine; Farrall, Andrew J.; Wardlaw, Joanna M.; White, Philip M.; Smith, Colin; Al-Shahi Salman, Rustam; Addison, Anne; Ahmad, Kate; Alhadad, Syed; Andrews, Peter; et al.
Abstract : Background and Purpose—: The characteristics of intracerebral hemorrhage (ICH) may vary by ICH location because of differences in the distribution of underlying cerebral small vessel diseases. Therefore, we investigated the incidence, characteristics, and outcome of lobar and nonlobar ICH. Methods—: In a population-based, prospective inception cohort study of ICH, we used multiple overlapping sources of case ascertainment and follow-up to identify and validate ICH diagnoses in 2010 to 2011 in an adult population of 695 335. Results—: There were 128 participants with first-ever primary ICH. The overall incidence of lobar ICH was similar to nonlobar ICH (9.8 [95% confidence interval, 7.7–12.4] versus 8.6 [95% confidence interval, 6.7–11.1] per 100 000 adults/y). At baseline, adults with lobar ICH were more likely to have preceding dementia (21% versus 5%; P =0.01), lower Glasgow Coma Scale scores (median, 13 versus 14; P =0.03), larger ICHs (median, 38 versus 11 mL; P <0.001), subarachnoid extension (57% versus 5%; P <0.001), and subdural extension (15% versus 3%; P =0.02) than those with nonlobar ICH. One-year case fatality was lower after lobar ICH than after nonlobar ICH (adjusted odds ratio for death at 1 year: lobar versus nonlobar ICH 0.21; 95% confidence interval, 0.07–0.63; P =0.006, after adjustment for known predictors of outcome). There were 4 recurrent ICHs, which occurred exclusively in survivors of lobar ICH (annual risk of recurrent ICH after lobar ICH, 11.8%; 95% confidence interval, 4.6%–28.5% versus 0% after nonlobar ICH; log-rank P =0.04). Conclusions—: The baseline characteristics and outcome of lobar ICH differ from other locations. Abstract : Supplemental Digital Content is available in the text.